Full–scale validation and implementation guidelines of combined piezoelectric sensing and big data analytics for long-term pavement performance monitoring - Manosalvas-Paredes, Mario (2021)
It is generally known that pavement structures, regardless of their main structural layer, start suffering progressive damage which could be either structural, functional or a combination of both from the day they are opened to traffic loading. This progressive damage may be exacerbated by different factors such as material properties, temperature, moisture, loading, tyre pressure, axle configuration, travel speed and so on. It is also known that road infrastructure very seldom becomes redundant in a country's economy and that for some, especially developing countries, road infrastructure is considered as one of their main assets and drivers of growth. Consequently, pavement deterioration has been widely studied at both laboratory and full-scale levels but despite of the multiple efforts made by researchers around the globe, there has not been a real application nor technology that could be easily implemented in the field.